Perilaku Siswa dan Pengguna Jalan di SMP Negeri 55 Kota Bekasi - Deslida Saidah; Tiur Mery Silalahi; Danang Darunanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
The research objective is to identify and analyze the behavior of drivers and road users in traffic in the absence of ZoSS when passing SMP Negeri 55 Bekasi City. The method used is quantitative descriptive qualitative method and with reference to the Director General of Land Transportation Regulation Number 1304 / AJ / 403 / DRJD / 2014 concerning School Safe Zones. The results showed that the behavior of students of SMP Negeri 55 Kota Bekasi and road users in times of heavy traffic without a School Safe Zone (ZoSS) made them unsafe and unsafe.